2020
DOI: 10.3390/nu12082322
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Consumption Patterns and Their Parent’s Perception of a Healthy Diet

Abstract: This study aims to examine children’s fruit, vegetable, and added sugar consumption relative to the Dietary Guidelines for Americans and the American Heart Association’s recommendations, as well as to compare children’s reported consumption with parental perception of the child’s overall diet quality. Data were drawn from 2 independent, cross sectional panels (2009–10 and 2014–15) of the New Jersey Child Health Study. The analytical sample included 2229 households located in five New Jersey cities. Daily consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Factors like quick lifestyle, a lack of proper health habits beginning at a young age, and reduced awareness are significant challenges the analysis found concerning reaching daily recommendations regarding fruit and vegetable intake. Eliason in 2020 noted that one source of reduced awareness concerning the study's recommendations is the parental perceptions of healthfulness that influence children's eating habits [11]. For instance, 45.92% of the study recorded a lack of constituency in fruit and vegetable daily recommendations through adopted practices, in most cases, from parents or guardians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors like quick lifestyle, a lack of proper health habits beginning at a young age, and reduced awareness are significant challenges the analysis found concerning reaching daily recommendations regarding fruit and vegetable intake. Eliason in 2020 noted that one source of reduced awareness concerning the study's recommendations is the parental perceptions of healthfulness that influence children's eating habits [11]. For instance, 45.92% of the study recorded a lack of constituency in fruit and vegetable daily recommendations through adopted practices, in most cases, from parents or guardians.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also recorded a mismatch of healthfulness between parents and children. Eliason highlight that 44% -65% of parent held the perception that their children consume daily recommendations despite the percentage presenting a mismatch through analysis of the children [11]. The mismatch originates from children's adaptation of dietary behaviors that disengage from healthier perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…National data as well as numerous other studies have consistently shown that children are not meeting fruit and vegetable recommendations [ 39 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. In contrast, most children in this study fell within the age and gender recommendations for fruit and vegetable intake, with 84% of the sample meeting at least the minimum MyPlate recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the public health messages promoting fruit and vegetable intake have penetrated this audience, leading to healthier intakes. Alternately, parents may have over-reported children’s fruit and vegetable consumption due to inaccurate estimations of intakes or, as seen in other studies, parents may have overestimated the healthfulness of their children’s diets, despite children not meeting recommendations [ 50 , 52 ]. Another possible explanation is that this study’s instrument aggregated fruits and vegetables—separating them may have revealed a differential effect for fruit vs. vegetables, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, children are not meeting the recommended daily intake of five serves of fruits and vegetables (F&V) combined [1][2][3][4]. In Australia, the most recent National Health Survey reported that 91.5% of children are not meeting their recommended intakes of two serves of fruit and five serves of vegetables/day [5].…”
Section: Introductionmentioning
confidence: 99%